The Use of English Central Application to Improve Students’ Speaking Skill - Maisyaroh Hasibuan; Benni Ichsanda Rahman Hz (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to investigate the effectiveness of the English Central application in improving junior high school students’ speaking skills, with specific objectives to (1) enhance students’ self-confidence in oral communication, (2) improve pronunciation accuracy and intonation, (3) increase learning motivation and engagement through gamified features, (4) foster learner autonomy and flexibility, and (5) develop fluency and vocabulary acquisition through authentic video-based content. Conducted over four weeks with 15 ninth-grade students, this research employed a mixed-method approach using observations, interviews, and questionnaires. Findings indicate notable improvements across multiple aspects: 86.6% of students reported greater self-confidence in speaking, while average pronunciation scores rose from 62 to 80. Fluency was enhanced as students extended their monologues from 40 seconds to 1 minute and 25 seconds, often incorporating idiomatic expressions such as by the way and in my opinion. Gamification elements fostered motivation, with most students completing 4–5 videos weekly, while flexibility encouraged independent practice outside the classroom. Additionally, 66.6% of students demonstrated learning autonomy by reviewing materials without teacher prompts. Despite these gains, challenges such as limited device access (26.6%), unstable internet connectivity, and decreased motivation in the fifth week were recorded, highlighting the need for varied materials and adaptive strategies. Overall, the results confirm that English Central is an effective supplementary tool for enhancing students’ speaking proficiency, aligning with communicative and learner-centered teaching principles.